Huge cardiac myxoma in pregnancy - Kuntharee Traisrisilp (2018)
© 2017 BMJ Publishing Group Ltd. All rights reserved. A 28-year-old pregnant woman presented at 28 weeks of gestation. She was diagnosed to have a left atrial myxoma 2 years earlier, but was lost to follow-up. During this pregnancy, the transthoracic echocardiography showed a 9 cm mass in the left atrium obstructing mitral valve inflow, interfering with mitral valve closure, causing severe mitral regurgitation and severe pulmonary hypertension. However, there were no clinical signs of pulmonary and systemic congestion or obstruction. Based on the clinical symptoms of the patient, the echocardiographic findings and the term of her pregnancy, the patient decided to schedule for a vaginal delivery with surgical correction after delivery. She gave birth at 32 weeks of gestation. During labour, pulmonary oedema developed but was detected early and it responded to therapy. Two weeks after delivery, a right anterior thoracotomy was performed to facilitate the removal of the left atrial myxoma and repair of the mitral valve.